Nitrogen-doped cobalt disulfide porous carbon nanotube as well as preparation method and application thereof
The preparation of nitrogen-doped cobalt disulfide porous carbon nanotubes through electrospinning and vulcanization treatment solves the problem of low specific capacity of carbon nanotubes and improves the sodium storage performance and cycle stability of the negative electrode material of sodium ion battery.
Patent Information
- Application Number
- CN202411791782.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-18
AI Technical Summary
As the negative electrode material of sodium ion battery, carbon nanotubes have a low specific capacity and are difficult to meet the needs of high-performance energy storage.
Nitrogen-doped cobalt disulfide porous carbon nanotubes were prepared by electrospinning, and porous structures were formed by urea doping heat treatment, and nitrogen-doped cobalt disulfide porous carbon nanotubes were obtained by vulcanization treatment.
It improves the sodium storage performance of carbon nanotubes, enhances the conductivity of the material and adsorption of sodium ions, extends the cycle life of the electrode material, and achieves high specific capacity and good cycle stability.
Smart Images

Figure CN119650633A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion batteries, and in particular relates to a nitrogen-doped cobalt disulfide porous carbon nanotube and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries (LIBs), as commercial energy storage products, have been widely infiltrated into human daily life. However, lithium resources are scarce and unevenly distributed on the earth. Therefore, finding a low-cost, resource-rich, high-performance secondary battery system to replace LIBs has become the key to sustainable energy development. Sodium and lithium belong to the same main group elements and show very similar properties, and sodium has the advantages of abundant reserves and low cost. Therefore, sodium-ion batteries (SIBs) have become one of the most likely systems to replace LIBs and are an important development direction for the development of energy storage devices in the future. Among them, carbon nanotubes have attracted much attention due to their unique morphology and structure, but they have problems such as low specific capacity that remain to be solved. Summary of the invention
[0003] The purpose of the present invention is to solve the problem of low specific capacity of carbon nanotubes as negative electrode materials of sodium ion batteries, and to provide a nitrogen-doped cobalt disulfide porous carbon nanotube and a preparation method and application thereof.
[0004] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0005] A method for preparing nitrogen-doped cobalt disulfide porous carbon nanotubes, the method comprising:
[0006] Step 1: dissolving polyacrylonitrile and a nitrogen source in N,N'-dimethylformamide to obtain a mixed solution;
[0007] Step 2: adding a cobalt source to the mixed solution of step 1 to obtain a spinning solution;
[0008] Step 3: electrospinning the spinning solution of step 2 to obtain electrospun nanofibers;
[0009] Step 4: heating the electrospun nanofibers in step 3 to 700°C under an inert atmosphere and calcining for 2h to obtain a Co3O4 / NCNFs composite material;
[0010] Step 5: Sulfurize the Co3O4 / NCNFs composite material obtained in step 4 to obtain a CoS2 / NCNFs composite material.
[0011] Further, in step 1, the dissolution is specifically as follows: stirring at 45°C for 6 hours, the N source is urea or thiourea, the mass ratio of urea to polyacrylonitrile is 0.2-0.4:1, the mass ratio of thiourea to acrylonitrile is 0.25-0.5:1, and the concentration of polyacrylonitrile in the mixed solution is 0.1 g ml -1 .
[0012] Furthermore, in step 2, the cobalt source is cobalt acetylacetonate or cobalt nitrate hexahydrate; the mass ratio of polyacrylonitrile to cobalt acetylacetonate is 1:1-0.6, and the mass ratio of polyacrylonitrile to cobalt nitrate hexahydrate is 1:0.8-0.5.
[0013] Furthermore, in step 3, the electrospinning is specifically performed by using a No. 17 electrospinning needle, a spinning voltage of 15-25 KV, a spinning temperature of 45-50°C, a distance between the needle hole and the roller collecting device of 18-22 cm, and a push injection speed of 0.08-0.12 mm min -1 .
[0014] Furthermore, in step 4, the inert atmosphere is argon or nitrogen, and the calcination heating rate is 5°C min -1 .
[0015] Furthermore, in step five, the sulfurization is specifically as follows: the Co3O4 / NCNFs composite material is mixed with sulfur element in a mass ratio of 1:3, and then placed in a tubular furnace, and maintained at 350°C for 2 hours under an inert atmosphere.
[0016] A nitrogen-doped cobalt disulfide porous carbon nanotube prepared by the above preparation method.
[0017] An application of nitrogen-doped cobalt disulfide porous carbon nanotubes prepared by the above preparation method in preparing negative electrode materials for sodium ion batteries.
[0018] A sodium ion battery comprises a negative electrode material, wherein the negative electrode material comprises the nitrogen-doped cobalt disulfide porous carbon nanotubes as described above.
[0019] The present invention utilizes electrospinning to prepare porous carbon nanotubes to encapsulate metal ions, and then gasifies the carbon nanotubes by urea doping and heat treatment to produce a porous structure, and obtains nitrogen-doped cobalt disulfide porous carbon nanotubes by sulfurization treatment. The network structure of nitrogen-doped cobalt disulfide porous carbon nanotubes further improves the sodium storage performance of carbon nanotubes. In general, the above technical solutions conceived by the present invention have the following gain effects compared with the prior art:
[0020] (1) The present invention uses polyacrylonitrile (PAN) as an electrospinning matrix, adds cobalt acetylacetonate as a cobalt source, and obtains a nitrogen-doped cobalt disulfide porous carbon nanotube (CoS2 / NCNFs) composite material with moderate pore size and uniform distribution through electrospinning and subsequent heat treatment. Nitrogen doping in carbon nanotubes can improve the conductivity of the material and its wettability to the electrolyte. At the same time, nitrogen atoms enhance the adsorption of sodium ions by the Lewis acid-base mechanism, thereby improving the sodium storage performance of the carbon material. The formation of a porous structure helps to improve the rapid transfer of ions, electrons and reactants.
[0021] (2) The present invention uses carbon nanotubes as the research object, realizes the composite of cobalt disulfide and porous carbon nanotubes through electrospinning and heat treatment, and further improves the sodium storage performance of carbon nanotubes. Composite metal sulfide materials can improve the material cycle specific capacity. Using metal sulfide as the negative electrode material of SIBs can enable it to obtain a higher theoretical specific capacity. Compared with the corresponding metal oxides, metal sulfides have smaller volume changes and have higher reversible specific capacity and mechanical stability.
[0022] (3) The porous structure can buffer the volume change caused by the reaction between metal sulfide and sodium ions. The strong conductivity of carbon fiber provides an effective electron transmission path for the transfer of electrons, thereby improving the conductivity of the electrode material and extending the cycle life.
[0023] (4) The present invention prepares CoS2 / NCNFs, and the preparation method is simple. The material is applied to the negative electrode material of sodium ion battery, and has excellent electrochemical performance, high specific capacity and good cycle stability. In the preferred embodiment of the present invention, when it is used as the negative electrode material of sodium ion battery, the current is 100mA. -1 At a current density of 1.5 Å, the discharge capacity is 301.6 mAh g after 100 charge and discharge cycles. -1 , providing important reference value for synthesizing electrode materials with high cycle stability and low cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 is a process flow chart of preparing CoS2 / NCNFs composite material in Example 1 of the present invention;
[0025] Figure 2 is an X-ray diffraction pattern of the CoS2 / NCNFs composite material prepared in Example 1 of the present invention;
[0026] Figure 3 is a 1 μm scanning electron microscope (SEM) image of the CoS2 / NCNFs composite material prepared in Example 1 of the present invention;
[0027] Figure 4 is a 200nm SEM image of the CoS2 / NCNFs composite material prepared in Example 1 of the present invention;
[0028] Figure 5 is a CV graph of the CoS2 / NCNFs composite material prepared in Example 1 of the present invention;
[0029] Figure 6 The CoS2 / NCNFs composite material prepared in Example 1 of the present invention is -1 Cycling performance diagram under current density;
[0030] Figure 7 The CoS2 / NCNFs composite material prepared in Example 1 of the present invention is -1 Cycling performance diagram under current density;
[0031] Figure 8 The CoS2 / NCNFs composite material prepared in Example 1 of the present invention is -1 Charge and discharge curves under current density;
[0032] Fig. 9 The CoS2 / NCNFs composite material prepared in Example 1 of the present invention is -1 Charge and discharge curves under current density. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0034] The present invention uses electrostatic spinning to prepare porous carbon nanotubes to encapsulate metal ions, and produces a porous structure on the surface and inside of the carbon nanotubes through urea doping and heat treatment gasification, and obtains nitrogen-doped cobalt disulfide porous carbon nanotubes through sulfurization treatment. The porous structure can buffer the volume change caused by the reaction of metal sulfide and sodium ions, the strong conductivity of carbon nanotubes provides an effective electron transmission path for the transfer of electrons, the metal sulfide improves the electrochemical performance, and the porous structure of the material provides more active sites, thereby improving the sodium storage performance of the battery.
[0035] Example 1
[0036] The experimental flow chart is as follows Figure 1As shown. Weigh 1g PAN as the electrospinning matrix, 0.8g cobalt acetylacetonate as the cobalt source, and 0.2g urea as the N doping, add them into 10ml DMF solvent, keep the temperature at 45℃, stir for 12h to form a uniform solution. The obtained solution is electrospun to obtain the precursor material. The electrospinning process is: use a No. 17 electrospinning needle, the spinning voltage is 20KV, the spinning temperature is 45-50℃, the distance between the needle hole and the roller collection device is 20cm, and the injection speed is 0.1mmmin -1 The precursor obtained by electrospinning was placed in a constant temperature tube furnace under a nitrogen atmosphere at 2°C min -1 The heating rate was raised to 300°C and then to 5°C min -1 The temperature was raised to 700 °C at a heating rate of 100 °C and kept at that temperature for 2 h to complete the high-temperature carbonization. The obtained product was recorded as Co3O4 / NCNFs.
[0037] The above Co3O4 / NCNFs material was mixed with sublimed sulfur in a mass ratio of 1:3 and placed in a constant temperature tube furnace under a nitrogen atmosphere. -1 The temperature was raised to 650 °C at a heating rate of 200 °C and kept at that temperature for 2 h to complete the sulfurization. The obtained product was recorded as CoS2 / NCNFs.
[0038] Electrochemical testing:
[0039] (1) Preparation of working electrode: Add an appropriate amount of 1-methyl-2-pyrrolidone to a mixture of PVDF, prepared active material and acetylene black (mass ratio of the three is 1:8:1), stir evenly to obtain electrode slurry. Use a coating scraper to evenly load the electrode slurry on copper foil, vacuum dry at 80℃ for 12h; use a slicer to make the dried copper foil into a circular working electrode (diameter 12mm).
[0040] (2) Button cell assembly: Assemble the battery in a glove box (water and oxygen contents are both below 0.1 ppm), place the working electrode / diaphragm (microporous polyethylene film) and counter electrode (sodium sheet) in the positive electrode shell in sequence, add an appropriate amount of electrolyte (1M NaPF6, EC / DMC=1:1 Vol%), then place the negative electrode shell and package it into a button cell.
[0041] (3) Electrochemical performance test: The CT2001A battery test system was used to test the cycle performance and rate performance of the battery, and the battery test window was 0.005-3.0 V. The electrochemical workstation (CHI760E) was used to perform cyclic voltammetry tests on the battery, with a voltage window of 0.005-3.0 V and a scan rate range of 0.2-1.0 mV s -1 The impedance spectrum of the battery was tested using an electrochemical workstation.
[0042] The X-ray diffraction pattern of the prepared CoS2 / NCNFs composite material is shown in Figure 2 The material is consistent with the characteristic peaks of the CoS2 standard card (JCPDS Card NO.41-1471), proving that the CoS2 carbon composite material was successfully synthesized. Figure 3 This is the 1μm SEM image of the CoS2 / NCNFs composite material. Figure 4 The SEM image is 200nm. The composite material shows a composite tubular structure, N doping creates pores in the tube, and CoS2 is coated in the carbon nanotubes. Figure 5 The CV graph of CoS2 / NCNFs composite is shown, and two reduction peaks are observed at 1.21 and 0.73 V, and two obvious oxidation peaks are observed at 1.94 and 2.23 V. However, in subsequent cycles, the reduction peaks shift to 1.45 and 0.81 V. The shift of the first cycle and subsequent reduction peaks may be due to the formation of SEI film. After the first cycle, the peaks are stable, indicating that the CoS2 / NCNFs composite has good stability.
[0043] The cycling performance of CoS2 / NCNFs composites is shown in Figure 6-7 shown. Figure 6 For CoS2 / NCNFs composites at 100mAg -1 Cyclic performance diagram at a current density of . After 100 cycles of charge and discharge, the discharge capacity is 301.6 mAh g -1 ; at 500mA g -1 The cycling performance diagram at the current density is shown in Figure 7 After 100 cycles of charge and discharge, the discharge capacity is 245 mAh g -1 . Figure 8 The charge-discharge curves of the CoS2 / NCNFs composite material for the first, second, 50th and 100th times at a current density of 100 mA g -1 The first discharge capacity is 814.2 mAh g -1 The first coulombic efficiency is 87.8%; at a current density of 500 mA g -1 hour( Fig. 9 ), the first discharge capacity is 708.2mAh g -1 , the first coulombic efficiency is 89.7%, showing good cycle stability, high capacity and coulombic efficiency.
[0044] Example 2
[0045] The implementation process of this embodiment is the same as that of embodiment 1. The difference is that the content of urea added is 0.1g. The composite material is -1At a current density of 1.5 200 mAh g, after 100 cycles of charge and discharge, the discharge capacity is 254.1 mAh g -1 ; at 500mA g -1 At a current density of 1.34 W, after 100 cycles of charge and discharge, the discharge capacity is 213.2 mAh g -1 .
[0046] Example 3
[0047] The implementation process of this embodiment is the same as that of embodiment 1. The difference is that the added urea content is 0.3g. The composite material is -1 At a current density of 1.547 W, after 100 cycles of charge and discharge, the discharge capacity is 243.8 mAh g -1 ; at 500mA g -1 At a current density of 1.5 mAh g, after 100 cycles of charge and discharge, the discharge capacity is 198.5 mAh g -1 .
[0048] Example 4
[0049] The implementation process of this embodiment is the same as that of embodiment 1. The difference is that the content of cobalt acetylacetonate added is 1g. The composite material is -1 At a current density of 1.547 W, after 100 charge and discharge cycles, the discharge capacity is 285.3 mAh g -1 ; at 500mA g -1 At a current density of 1.547 W, after 100 cycles of charge and discharge, the discharge capacity is 223.6 mAh g -1 .
[0050] Example 5
[0051] The implementation process of this embodiment is the same as that of embodiment 1. The difference is that the content of cobalt acetylacetonate added is 0.6 g. The composite material is -1 At a current density of 1.5 mAh g, after 100 cycles of charge and discharge, the discharge capacity is 293.5 mAh g -1 ; at 500mA g -1 At a current density of 100 cycles, the discharge capacity is 232 mAh g -1 .
[0052] In the above embodiments, different contents of nitrogen-containing polymer and cobalt acetylacetonate were selected to obtain CoS2 / NCNFs composite materials, among which the experimental effect of embodiment 1 was the best.
[0053] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing nitrogen-doped cobalt disulfide porous carbon nanotubes, characterized in that: The method is: Step 1: dissolving polyacrylonitrile and a nitrogen source in N,N'-dimethylformamide to obtain a mixed solution; Step 2: adding a cobalt source to the mixed solution of step 1 to obtain a spinning solution; Step 3: electrospinning the spinning solution of step 2 to obtain electrospun nanofibers; Step 4: heating the electrospun nanofibers in step 3 to 700°C under an inert atmosphere and calcining for 2h to obtain a Co3O4 / NCNFs composite material; Step 5: Sulfurize the Co3O4 / NCNFs composite material obtained in step 4 to obtain a CoS2 / NCNFs composite material.
2. The method for preparing nitrogen-doped cobalt disulfide porous carbon nanotubes according to claim 1, characterized in that: In step 1, the dissolution is specifically as follows: stirring at 45°C for 6 hours, the N source is urea or thiourea, the mass ratio of urea to polyacrylonitrile is 0.2-0.4:1, the mass ratio of thiourea to acrylonitrile is 0.25-0.5:1, and the concentration of polyacrylonitrile in the mixed solution is 0.1 g ml -1 .
3. The method for preparing nitrogen-doped cobalt disulfide porous carbon nanotubes according to claim 1, characterized in that: In step 2, the cobalt source is cobalt acetylacetonate or cobalt nitrate hexahydrate; the mass ratio of polyacrylonitrile to cobalt acetylacetonate is 1:1-0.6, and the mass ratio of polyacrylonitrile to cobalt nitrate hexahydrate is 1:0.8-0.
5.
4. The method for preparing nitrogen-doped cobalt disulfide porous carbon nanotubes according to claim 1, characterized in that: In step 3, the electrospinning is specifically as follows: a No. 17 electrospinning needle is used, the spinning voltage is 15-25KV, the spinning temperature is 45-50°C, the distance between the needle hole and the roller collection device is 18-22cm, and the injection speed is 0.08-0.12mmmin -1 .
5. The method for preparing nitrogen-doped cobalt disulfide porous carbon nanotubes according to claim 1, characterized in that: In step 4, the inert atmosphere is argon or nitrogen, and the calcination heating rate is 5°C min -1 .
6. The method for preparing nitrogen-doped cobalt disulfide porous carbon nanotubes according to claim 1, characterized in that: In step 5, the sulfurization is specifically as follows: the Co3O4 / NCNFs composite material is mixed with sulfur element in a mass ratio of 1:3, and then placed in a tubular furnace, and maintained at 350°C for 2 hours under an inert atmosphere.
7. A nitrogen-doped cobalt disulfide porous carbon nanotube prepared by the preparation method according to any one of claims 1 to 6.
8. Use of nitrogen-doped cobalt disulfide porous carbon nanotubes prepared by the preparation method according to any one of claims 1 to 6 in preparing negative electrode materials for sodium ion batteries.
9. A sodium ion battery, characterized in that: It comprises a negative electrode material, wherein the negative electrode material comprises the nitrogen-doped cobalt disulfide porous carbon nanotube as claimed in claim 8.